Fibrolipoma with Osseous and Cartilaginous Metaplasia of Hoffa's Fat Pad: A Case Report. (2nd August 2012) - Gigis, Ioannis; Gigis, Panagiotis
Abstract : The most common benign tumors of the mesenchyme are the lipomas. Benign fatty tumors can arise in any location in which fat is present. Fibrolipomas are characterised by fat modules. Most patients affected by such tumors are in the fifth or sixth decade of life. When very close to vital structures such as joints, they may cause functional limitations as well as pain. Osseous and chondroid metaplasia can infrequently manifest after chronic persistence. Given the rarity of this condition, a case of a big fibrolipoma of Hoffa's fat pad with osseous and cartilaginous metaplasia is reported. A 44-year-old woman presented with an enlarging soft mass on the right knee in the infrapatellar fat pad. After a thorough preoperative clinical and imaging examination, the mass was removed and sent to laboratory where the diagnosis was put. One year after surgery, both local and general condition of the patient were good and no signs of recurrence were found.